2019
DOI: 10.1126/science.aav2572
|View full text |Cite
|
Sign up to set email alerts
|

Particulate methane monooxygenase contains only mononuclear copper centers

Abstract: Bacteria that oxidize methane to methanol are central to mitigating emissions of methane, a potent greenhouse gas. The nature of the copper active site in the primary metabolic enzyme of these bacteria, particulate methane monooxygenase (pMMO), has been controversial owing to seemingly contradictory biochemical, spectroscopic, and crystallographic results. We present biochemical and electron paramagnetic resonance spectroscopic characterization most consistent with two monocopper sites within pMMO: one in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
294
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(335 citation statements)
references
References 67 publications
24
294
2
1
Order By: Relevance
“…10 Oxo-bridged copper centers have been proposed (but recently called into question, vide infra) as intermediates in the oxidation of methane to methanol by pMMO. 42 Sequential isothermal treatments of 3% N 2 O in He followed by ow of CH 4 for one hour at 150 C resulted in the formation of methanol with productivities ranging from $1.5-2.5 mmol MeOH per mol Cu dependent on the imidazole ligand (Table 1), with no loss of MOF crystallinity. A Cu 2 O 2 active site proposed from density functional theory (DFT) was supported by X-ray absorption spectroscopy.…”
Section: Methane and Ethanementioning
confidence: 97%
See 1 more Smart Citation
“…10 Oxo-bridged copper centers have been proposed (but recently called into question, vide infra) as intermediates in the oxidation of methane to methanol by pMMO. 42 Sequential isothermal treatments of 3% N 2 O in He followed by ow of CH 4 for one hour at 150 C resulted in the formation of methanol with productivities ranging from $1.5-2.5 mmol MeOH per mol Cu dependent on the imidazole ligand (Table 1), with no loss of MOF crystallinity. A Cu 2 O 2 active site proposed from density functional theory (DFT) was supported by X-ray absorption spectroscopy.…”
Section: Methane and Ethanementioning
confidence: 97%
“…40 Leading structural proposals for the active sites invoke mono or dinuclear copper centers in pMMO, and dinuclear iron sites in sMMO. [41][42][43] These motifs are found in a variety of Cu/Fe MOF SBUs and have accordingly been investigated for methane/ ethane oxidation activity. Other examples of alkane oxidation by abiological metals and/or oxidizing metal species (e.g.…”
Section: Methane and Ethanementioning
confidence: 99%
“…In comparison to the iron based active centers in sMMO, pMMO contains a catalytic copper center [13,35]. In a recent report, Ross et al [36] reported that pMMO consists of two mono-copper active sites, having an assembly of protein sub-units, PmoB and PmoC, for methane binding and oxidation [36]. According to their study, methane oxidation to methanol in pMMO occurs in the presence of an electron donor, formaldehyde dehydrogenase (FADH), which generates hydrogen peroxide (H 2 O 2 ) at the PmoB site.…”
Section: Dmtm In Naturementioning
confidence: 99%
“…2a, Supplementary Fig. 9 ) 9 and required for O 2 binding and methane oxidation 26 . Interestingly, the bacterial and phage-associated PmoC sequences were generally very similar in the central membrane-and periplasmic associated portions, but divergent at the cytoplasmic N-and C-termini.…”
Section: Phages With Standalone Pmoc Genesmentioning
confidence: 99%
“…Although possibly acquired from bacterial hosts along with other genes, only pmoC was retained as it can enhance phage fitness alone. In bacterial methanotrophs, there is increasing evidence indicating the essential role of PmoC in methane oxidation and the absolute necessity of PmoB is questionable 12,25,26,40 . Given that the structure of PmoC is susceptible and largely disordered when the cell membrane is perturbed 41 , we suggest that the additional pmoC genes either in the bacterial methanotroph or phage genome ( Supplementary Table 3 ) could sustain methane oxidation under abnormal conditions.…”
Section: Why Only Pmoc In Phages?mentioning
confidence: 99%